An Empirical Analysis of Profitability Determinants and Cost Efficiency of Commercial Banks in China - Fu, Rong (2015)
Abstract During the period 2009-2014, the overall performance of China’s banking sector is decline. The recession is mainly due to the international and Chinese economic turmoil. The purpose of this study is to investigate the determinants of profitability and cost efficiency for 30 commercial banks operating in China during the examination period 2009-2014. Under the estimation of GMM, all bank-specific determinants have a positive relationship with bank performance, while all macroeconomic factors are negatively correlated with profitability. Cost efficiency, which is one of the essential determinants of interpreting bank profitability estimated by SFA shows a decline over time.